Pergolakan Teologi Syiah-Sunni: Membedah Potensi Integrasi dan Disintegrasi - Slamet Mulyono (Ulumuna, 2012)
Shia-Sunni conflict in Sampang Madura recently, and that happens greased with political strife in Syria to date, suggests that the dynamics of the Shia-Sunni relations is still turbulent. This paper will elaborate aspects of conflict in two major streams in Islam, while also exposing the sides of the similarities between them. There are five issues targeted in this study, namely: the imāmah, the authenticity of the Qur'an, the khilāfah of Abū Bakr, the right to the khilāfah of ‘Ali ibn Abi Ṭālib, and the meaning of ahl al-bayt. The authors conclude that the differences in the two streams in the issues range from highly-diametric, put forward by the extreme sects, to the subtle differences and almost in tune, put forward by a moderate sects.